THE CONCEPT RESEARCH OF DEVELOPMENT PEDAGOGICAL COMPETENCE OF A FUTURE TEACHER OF PSYCHOLOGY IN MAGISTRACY - Cherepekhina Olha (Неперервна професійна освіта: теорія та практика)
future teacher of psychology in a magistracy. Author build their own concept of further research based on such scientifictheoretical and methodological foundations such as: axiological; acmeological; activity; competence, professionography; system, personal and human-centered approaches. It is established that the phenomenon of pedagogical competence was studied by scientists from various conceptual approaches, which allowed the author to build his own concept of further research, based on scientific, theoretical and methodological principles.